Licorice and Arrhythmia: A Case Report - Bahram Mehrtash; Marzieh Beygom Siahpoosh; Majid Hajikarimi (Tehran University of Medical Sciences, 2017)
Licorice is a popular herb in herbal medicine specially to treat gastric ulcers. It is one of the most widely prescribed herbs in Persian medicine. Excessive consumption of licorice may lead to cardiac arrhythmia due to a hyper mineralocorticoid state and hypokalemia. In a 22-year-old man from Iran, with no prior history of cardiovascular disease, sinus arrhythmia occurred after using average dose of licorice for Irritable bowel syndrome without hypokalemia. According to Persian medicine, this case owned a hot temperament of heart so, licorice for this patient was not a good choice to treat his Irritable bowel syndrome because its temperament is hot and it could make the temperament of this patient's heart hotter and even result in faint. Neglecting from Individual features such as heart temperament, especially in addition to existence of sensitizer factors may lead patient to show cardiac arrhythmia without hypokalemia after using of licorice in average dose. This evidence belongs to only one case and actually, to receive a strong conclusion, more essential studies are required but it could be an evidence to think about evaluation the safety of licorice. It seems that our knowledge about herbal medicine is not so enough so we should use them with caution.